A trypsin inhibitor from Moringa oleifera flower extract is cytotoxic to Trypanosoma cruzi with high selectivity over mammalian cells - Pontual, Emmanuel V.; Pires-Neto, Divar F.; Fraige, Karina [UNESP]; Higino, Taciana M. M.; Carvalho, Belany E. A.; Alves, Neyla M. P.; Lima, Thamarah A.; Zingali, Russolina B.; Coelho, Luana C. B. B.; Bolzani, Vanderlan S. [UNESP]; Figueiredo, Regina C. B. Q.; Napoleao, Thiago H.; et al. (Taylor & Francis Ltd, 2018)
In this study, Moringa oleifera flower extract and a trypsin inhibitor (MoFTI) isolated from it were evaluated for anti-protozoal activity against Trypanosoma cruzi and cytotoxicity to mammalian cells. The presence of flavonoids was remarkable in the HPLC fingerprints of the extract at 254 and 360 nm. Amino acid sequences of peptides derived from in-gel digestion of MoFTI were determined. Both the extract and MoFTI caused lysis of T. cruzi trypomastigotes with LC50/24 h of 54.18 +/- 6.62 and 41.20 +/- 4.28 mu g/mL, respectively. High selectivity indices (7.9 to >12) for T. cruzi cells over murine peritoneal macrophages and Vero cells were found for the extract and MoFTI. The results show that MoFTI is a trypanocidal principle of the flower extract. [GRAPHICS] .
Keywords: Moringa oleifera; chagas disease; protease inhibitor; trypomastigote; cytotoxicity